Protective effects and mechanisms of Terminalia catappa L. methenolic extract on hydrogen-peroxide-induced oxidative stress in human skin fibroblasts - Ya-Han Huang; Po-Yuan Wu; Kuo-Ching Wen; Chien-Yih Lin; Hsiu-Mei Chiang (BMC, 2018)
Abstract Background Oxidative stress plays a crucial role in aging-related phenomenon, including skin aging and photoaging. This study investigated the protective role and possible mechanism of Terminalia catappa L. methanolic extract (TCE) in human fibroblasts (Hs68) against hydrogen peroxide (H2O2)-induced oxidative damage. Methods Various in vitro antioxidant assays were performed in this study. The effect and mechanisms of TCE on oxidative stress-induced oxidative damage were studied by using western blotting. Results The IC50 of TCE was 8.2 μg/mL for 1,1-diphenyl-2-picrylhydrazyl radical scavenging, 20.7 μg/mL for superoxide anion radical scavenging, 173.0 μg/mL for H2O2 scavenging, 44.8 μg/mL for hydroxyl radical scavenging, and 427.6 μg/mL for ferrous chelation activities. Moreover, TCE inhibited the H2O2-induced mitogen-activated protein kinase signaling pathway, resulting in the inhibition of c-Jun, c-Fos, matrix metalloproteinase (MMP)-1, MMP-3, MMP-9, and cyclooxygenase-2 expression. TCE also increased hemeoxygenase-1 expression inhibited by H2O2. Finally, TCE was demonstrated reverse type I procollagen expression in fibroblasts after H2O2 treatment. Conclusions According to our findings, TCE is a potent antioxidant and protective agent that can be used in antioxidative stress-induced skin aging.